BALANCING OF ROTORS WITH HINGED WORKING PARTS - Oleg O. Polushkin; Oleg A. Polushkin; Viktor P. Zharov (Advanced Engineering Research)
Generalized rational technology of the rotors with hinged working parts is developed. Their balancing speed is a priori established, that enables to formalize the technological preparation of those rotors balancing.